Pelican sketchbook - Frith, Julia (Cengage Learning Australia South Melbourne, Vic., 1994)
Pelican Sketchbook is a captivating artistic collection that showcases the beauty of pelicans through sketches and illustrations. Featuring a variety of artistic styles, this book highlights the grace and charm of these coastal birds, capturing their unique characteristics and habitats. Alongside the artwork, insightful commentary provides information about pelican behavior, ecology, and their significance in the ecosystem. This sketchbook serves as both an art resource and an educational tool, inspiring nature lovers and artists alike to appreciate the elegance of pelicans and the natural world.